Degrowth in an African periphery: Recentring decoloniality around circular ontologies - Ngam, Roland (New Agenda: South African Journal of Social and Economic Policy, 2024)
In this article Roland Ngam focuses on Africa and the disarticulated colonial model on which it is built and argues that in order to build a fairer system that works for the majority, the world needs to quickly shift to an ecocentric degrowth ontology that leverages Africa’s rich cultural heritage for the wellbeing of all people.